PLURALITAS METODE PEMBERIAN SUARA: DISHARMORNI TRADISI LOKAL DALAM MEWUJUDKAN INKLUSIVITAS PEMILU - Darmawan, Devi (Faculty of Law Jenderal Soedirman University, 2014)
Procedural rules of electoral law require the application of the principle of equality in the electoral process. Ironically, The Constitutional Court has created the plurality law on suffrage methods in electoral districts through legalized traditional value of the local society. The problematic appears when its methods could not fulfill the principle of democratic elections and also increase the potency to set the electoral law at deviance, especially in voting stage. Therefore, without any intention to neglect the existence of traditional local cultures, this paper will explain the relevant of plurality of law on suffrage methods to achieve an inclusive election process.Key words: democratic electoral, plurality law, voting methods